Biochar strengthens rainfall regime resistance of soil inorganic C by enhancing pH–bicarbonate and carbonic anhydrase regulation in dryland region - Yuhao Wang; Yanbo Ji; Shutong Guo; Lin Sun; Enke Liu; Zhikuan Jia; Kadambot H.M. Siddique; Rui Qian; Ting Wei; Peng Zhang (Agriculture, Ecosystems & Environment, 2026)

Recovery of acid-grade calcium fluoride from fluorine‑silicon-containing wastewater using ammonia solution desilication and calcium carbonate precipitation: Effects, dissociation mechanisms and application potential - Tong Zhao; Huifen Yang; Dong Lin; Yuhao Liang; Siqi Zhang; Guocui Li; Qiwei Sun (Journal of Water Process Engineering, 2026)

Piezoelectric-photocatalysis assisted chemical mechanical polishing: A cost-effective and efficient approach to atomic-scale processing of RS-SiC surfaces - Xingwang Xu; Jiayi Liu; Bin Lin; Tianyi Sui; Jinming Li; Bingrui Lv; Pengcheng Zhao; Hetian Hou; Cong Chen; Hualong Zhang; Yuhao Zhang; Jinhua Wei; et al. (Journal of Environmental Chemical Engineering, 2026)

A tetrahedral framework DNA-metformin nano-firefighter for quenching adipose chronic inflammation: Reprogramming macrophages to restore metabolic homeostasis in obesity - Zhuo Chen; Jiaqi Li; Alimire Alifu; Fenglin Jiang; Wenjing Tang; Zaowei Yang; Yuhao Liu; Bo Tian; Xi Chen; Yu Chen; Qi Han; Yunfeng Lin (Chemical Engineering Journal, 2026)

Flood exposure and suicide risk in Japan, 2008–2022: a nationwide study - Gengchao Lin; Yuhao Xu; Bingda Liao; Hang Yu (Environmental Research, 2026)

Harnessing white-light-emitting metal-organic frameworks for efficient and UV-stable perovskite solar cells - Wei Wang; Xingrui Zhang; Jian Zhang; Jiaqi Wang; Boyuan Hu; Yuhao Xiong; Kaifeng Lin; Debin Xia; Yulin Yang (Chemical Engineering Journal, 2026)

Next-generation multiplex food allergen sensing: From PDMS microfluidic prototypes toward intelligent industrial systems - Xin Zhao; Mengfei Deng; Yuhao Huang; Wenjia Zhu; Lili Xu; Hong Lin; Zhenxing Li (Trends in Food Science & Technology, 2026)

A new sesterterpenoid with β -glucuronidase inhibitory activity from the Cordyceps -colonising fungus Aspergillus versicolour ZJUTE2 - Youmin Ying; Yixian Qiu; Jing Tang; Yuhao Lin; Sha Xu; Jiayue Ni; Yun Zhang; Cuiping Tong; Wei Mao (Natural Product Research, 2026)

Constructed wetlands with recycled glass pumice as substrate: Application in eel recirculating aquaculture systems - Jinghong He; Jiemei Wang; Jinzhi Zou; Hoi Leong Lee; Yanan Chen; Qiaodan Gan; Rongtai Lin; Junlv Chen; Ding Yuan; Yuhao Zhou (Chemical Engineering Journal, 2026)

A sustained-release antibacterial gelatin hydrogel based on metal-phenolic networks for long-term preservation of prefabricated meat - Yanan Liu; Yuhao Huang; Qileng Aori; Yu Wang; Sai Zhao; Zhen-Lin Xu (Food Chemistry, 2026)

A Novel Long-range Excitatory Neural Circuit from the Magnocellular Red Nucleus to Spinal Dorsal Horn Facilitates Neuropathic Pain-like Behaviors in Male Mice - Jiali Shi; Yinfeng Yuan; Yuhao Luo; Yue Guo; Jiashu Lian; Lin Lin; Danni Chen; Qian Wang; Xiumin Xue; Zhichao Chen; Yongjie Wang; Zhihui Huang (Neuroscience Bulletin, 2026)
Neuropathic pain arises from a primary lesion or disease affecting the somatosensory system; however, the brain circuitry underlying the regulation of neuropathic pain remains unclear. The red nucleus (RN) is a critical brain region involved in regulating muscle tension, coordinating movement, and facilitating sensorimotor integration. While some evidence has shown that RN regulates pain, its specific role in neuropathic pain and associated neural circuits remains elusive. In this study, we found that CaMKIIα-positive neurons in the magnocellular red nucleus (RMC CaMKIIα ) were activated following common peroneal nerve (CPN) ligation-induced chronic neuropathic pain in adult male mice. Interestingly, chemogenetic and optogenetic inhibition of these RMC CaMKIIα neurons alleviated the thermal hyperalgesia and mechanical allodynia in the neuropathic pain model mice, whereas activation of these neurons sufficiently induced the mechanical allodynia and thermal hyperalgesia in naïve mice. Trans-synaptic viral tracing studies further revealed that long-range CaMKIIα + neuron projections from RMC to the dorsal horn (DH) facilitated the neuropathic pain-like behaviors following CPN ligation. DH neurons received direct innervation from RMC CaMKIIα neurons, and inhibition of RMC CaMKIIα -DH CaMKIIα circuits alleviated the neuropathic pain in the ligated mice. Taken together, these results identify a novel long-range excitatory neural circuit from RMC to DH that facilitates the neuropathic pain-like behaviors in adult male mice, providing a new target for neuropathic pain treatment.

Pasteurella multocida toxin induces apoptosis of respiratory epithelial cells by activating the PERK–NF-κB-DR5 signaling axis - Fei Wang; Yuhao Lei; Menghan Chen; Haixin Bi; Yayuan Luo; Fangfang Bai; Lin Hua; Huanchun Chen; Qigai He; Bin Wu; Zhong Peng (Veterinary Microbiology, 2026)

Exploring the impact of dietary extracellular vesicles on gut health: homeostasis, barrier defense, immunity, and signaling pathways - Haiyan Zhang; Jianing Tu; Yue Pang; Jiahui Ma; Lin Zhang; Chenyu Xue; Yuhao Liu; Weichen Hong; Mizhou Hui; Bailiang Li; Na Dong; Chenzhe Gao (Food Research International, 2026)

Integrating very-high-resolution imagery, Sentinel-2 time-series data, and machine learning to map shrub fractional abundance across arid and semi-arid ecosystems in China - Zhonghua Liu; Yuhao Feng; Xin Cao; Josep Peñuelas; Adrià Descals; Daryl Yang; Ka Kin Cheung; Shuwen Liu; Ziyu Lin; Xiaoqiang Liu; Xiaoyong Wu; Han Ma; et al. (Remote Sensing of Environment, 2026)

Corrigendum to “An oxidized dextran-composite self-healing coated magnesium scaffold reduces apoptosis to induce bone regeneration” [Carbohydrate Polymers 327 (2024) 121666] - Zewen Shi; Fang Yang; Yiwei Hu; Qian Pang; Lin Shi; Tianyu Du; Yuhao Cao; Baiyang Song; Xueqiang Yu; Zhaoxun Cao; Zhewei Ye; Chen Liu; et al. (Carbohydrate Polymers, 2026)

Development and application of fluorescent immunoassay lateral flow Technology for the Detection of Prolamins in food - Xinyi Zhao; Qi Fu; Wenye Zhu; Hong Lin; Zhiyu Liu; Hao Wang; Phon Reno; Ziye Zhang; Yuhao Huang; Zhenxing Li (Food Chemistry, 2026)

Insight into the internal microscopic structure and composition of aerobic granular sludge under high salinity based on high-resolution Micro-CT technology - Yuhao Tong; Aqiang Ding; Jun Liu; Lin Quan; Hao Liu; Fuzhong Song; Demin Yang; Daijun Zhang; Peili Lu (Environmental Research, 2026)

CFD data-driven CNN-LSTM for fast prediction of instantaneous flow characteristics in hydrocyclones - Dianyu E; Yuhao Zhang; Hongwei Hu; Guangtai Xu; Lin Liu; Jiaxin Cui; Cong Tan; Ruiping Zou; Shibo Kuang (Minerals Engineering, 2026)

Advancing bidirectional hydrogen spillover in heterostructure catalysts for electrocatalytic antimony removal and recovery from wastewater - Yuhao Lin; Yanling Wu; Xiaojia Jiang; Qi Wang; Yanbiao Liu; Limin Jin (Journal of Hazardous Materials, 2026)

Cold exposure triggers distinct RNA editing, alternative splicing, and gene expression patterns in cold domestication pufferfish (Takifugu obscurus) - Shuang Han; Jie Wang; Yuhao Luo; Jingping Zhang; Youquan Wang; Taixing Lin; Boyan Xu; Qigen Liu; Liangbiao Chen (Fish & Shellfish Immunology, 2026)

Mechanisms of bioelectrochemistry enhanced saline aerobic granular sludge: From EPS monomers to microbial metabolism - Aqiang Ding; Shikang Li; Wenkai Yao; Yuhao Tong; Lin Quan; Chun Yang; Fuzhong Song; Daijun Zhang; Peili Lu (Chemical Engineering Journal, 2026)

Extraction, structural characterisation, antioxidant, and hypoglycaemic activity of polysaccharides from Floccularia luteovirens - Wei Feng; Yuhao Cui; Yaqi Tian; Junlong Wang; Yonggang Lin; Wen-Pan Shi (Natural Product Research, 2025)

Paeoniflorin attenuates hyperprolactinemia by targeting the pituitary mPRα-mediated, dopamine receptor-independent signaling in vivo and in vitro - Bingqi Lin; Yun Yi; Xiaolan Mo; Yifan Yang; Yuhao Li; Chunxia Wang; Yuanyi Wei (Toxicology and Applied Pharmacology, 2025)

Biomass-derived activated carbon-supported CuZnOS bimetallic oxysulfide catalyst with highly efficient catalytic reduction of organic and hexavalent chromium pollutants - Jiqing Li; Yuanbo Guo; Kening Xiang; Haoyu Wang; Tao Liu; Cuizhu Li; Zhenjie Wu; Yuhao Hong; Dong-Hau Kuo; Dongfang Lu; Jinguo Lin; Xiaoyun Chen (Journal of Environmental Chemical Engineering, 2025)

Efficient preparation of large-area anisotropic graphite films with high thermal conductivity and excellent electromagnetic shielding performance - Zhihong Han; Mingyi Tan; Daming Chen; Wenzheng Zhang; Zhipeng Lin; Jiahui Zhou; Yuhao Fang; Shengze Zhang; Qihong Wei; Xinghong Zhang; Wenbo Han (Chemical Engineering Journal, 2025)

Predicting internal carotid artery system risk based on common carotid artery by machine learning - Yuhao Tong; Qingyi Zhang; Feng Zhang; Weidong Mu; Steven W. Su; Lin Liu (Medical & Biological Engineering & Computing, 2025)

Seawater Flow-Freezing Characteristics in Open Container Injection Under Low-Temperature Conditions - Yuhao Fan; Bei Peng; Puyu Jiang; Jiahui Ren; Yuesen Lin; Longlong Gao; Baoren Li (Journal of Marine Science and Engineering, 2025)
The phenomenon of seawater flow-freezing exists during ballast water injection and drainage in polar vessels, but the heat transfer and ice evolution behaviors under low-temperature flow conditions remain unclear. This study developed a computational model for ballast tank freezing using the volume of fluid (VOF) and enthalpy–porosity method, and constructed a scaled experimental platform for the simulation model validation. Based on this model, the flow-heat transfer and ice evolution process in the ballast tank are analyzed in detail, with a focus on the influence of injection velocity, pipe diameter, and position on seawater freezing characteristics. The results show that during low-temperature water injection, phase change occurs preferentially in the tank bottom region, with ice presenting as a slurry morphology; when injection velocity increases from 0.25 m/s to 3.5 m/s, the maximum ice-phase volume fraction increases by 48.9%, indicating faster flow accelerates phase-change freezing; compared to other diameters, DN150 piping exhibits the highest turbulent kinetic energy (0.054 m2/s2) and the maximum shear stress (12.49 Pa), demonstrating optimal freezing resistance; compared to bottom injection, sidewall injection intensifies heat transfer/icing near tank walls and increases ice-clogging risk around ports. This study reveals intrinsic mechanisms of dynamic ice-blockage evolution, providing theoretical basis for anti-clogging design in polar ship systems.

Community and functional succession of corrosive microorganisms during flowback and produced water management in Sichuan Basin - Jiayi Qing; Aqiang Ding; Zhengming Hou; Lin Quan; Yuhao Tong; Junou Pan; Xiong Li; Peili Lu (Journal of Water Process Engineering, 2025)

Ganodermanic acid, a new steroidal compound derived from the marine fungus Aspergillu s sp. ZJUT223 - Youmin Ying; Xiaoxiao Chen; Shijie Zhan; Si Yang; Jinli Liu; Weiguang Shan; Yuhao Lin; Rong Wang (Natural Product Research, 2025)

Tree species classification via a two-stage deep learning framework: integration of enhanced spectral reconstruction with classifiers - Zhiping Lin; Yuhao Yuan; Qun Zang; Zhongmou Fan (International Journal of Remote Sensing, 2025)

Long-term variations in the ratio of transpiration to evapotranspiration and their drivers in a humid subalpine forest - Yuhao Xiang; Genxu Wang; Arthur Gessler; Xiangyang Sun; Shan Lin; Zishu Tang; Shouqin Sun; Zhaoyong Hu (Agricultural and Forest Meteorology, 2025)

Microbial community structure and functional characteristics in shale gas flowback water from marine shale formation in Sichuan Basin, China: Insights into C-N-P-S cycle and correlations - Lin Quan; Aqiang Ding; Jun Liu; Yuhao Tong; Jiayi Qing; Junou Pan; Xiong Li; Bin Lei; Daijun Zhang; Peili Lu (Journal of Water Process Engineering, 2025)

Improving water/ice/snow depth accuracy on runway pavement with ultrasonic echo signal analysis - Yuhao Chen; Jin Wu; Dadi Lin; Pengpeng Yan; Ziyu Ji; Jinzhong Zhao; Jinxing Cheng (Cold Regions Science and Technology, 2025)

ROS acted as an initial role in selenium nanoparticles alleviating insecticide chlorpyrifos-induced oxidative stress, pyroptosis, and intestinal barrier dysfunction in porcine intestinal epithelial cells - Minna Qiu; Zhiyu Hao; Yuhao Liu; Yuhang Liu; Minghang Chang; Xu Lin; Xiumei Liu; Na Dong; Wei Sun; Xiaohua Teng (Pesticide Biochemistry and Physiology, 2025)

Insights into effects of processing and food matrices on structure and ELISA detection of sarcoplasmic calcium binding protein - Wenye Zhu; Qingwen Liu; Yuhao Huang; Hao Wang; Hang Lin; Xiang Gao; Hong Lin; Zhenxing Li (Food Chemistry, 2025)

Impact of flow configuration on microbial ecological processes and health risks in biological activated carbon filters - Zedong Lu; Yazhou Sun; Xing Li; Yuhao Xie; Xinyu Lin; Jiawei Ren; Zhiwei Zhou (Chemical Engineering Journal, 2025)

Two-stage inoculation with lignocellulose-degrading microorganisms in composting: Enhanced humification efficiency and underlying mechanisms - Yu Zhang; Binfeng Lin; Yuhao Hao; Mengling Lu; De Ding; Shiyuan Niu; Hongquan Xiang; Zhi Huang; Jianbin Li (Environmental Research, 2025)

Bioassay-guided isolation and characterisation of α-glucosidase inhibitors from Sanghuangporus baumii - Xiaoyan Hu; Yanling Wang; Yuhao Lin; Nini Yang; Junyi Yao; Weiguang Shan; Guiwei Rao; Youmin Ying (Natural Product Research, 2025)

Insights into nitrogen metabolism and humification process in aerobic composting facilitated by microbial inoculation - Binfeng Lin; Yu Zhang; Yuhao Hao; Mengling Lu; Hongquan Xiang; De Ding; Shiyuan Niu; Kai Li; Jianbin Li; Zhi Huang (Environmental Research, 2025)

Enhancing natural carbon sinks: Simulation of land use change under different carbon market scenarios by developing an ANN-ABM model - Ruimin Lin; Ru Guo; Yunyang Li; Guanghui Shao; Yuhao Zhang; Kaiming Peng; Xiangfeng Huang (Resources, Conservation and Recycling, 2024)

Methods for detecting green tide in the Yellow Sea using Google Earth Engine platform - Yuhao Shang; Lingling Jiang; Lin Wang; Zixu Ye; Siwen Gao; Xiaohui Tang (Regional Studies in Marine Science, 2024)

Understanding the role of topography on valley floor gully and hillslope gully development in cropland of the rolling hill region of northeast China - Yuhao Gao; Yifan Zhu; Junxi Chen; Yiting Huang; Yangbo He; Zhengchao Tian; Lirong Lin; Chongfa Cai; Jiazhou Chen (Geomorphology, 2024)

Specific detection of crustacean allergens in food: Development of indirect competitive and sandwich ELISA targeting sarcoplasmic calcium binding protein - Wenye Zhu; Zhihui Qin; Yuhao Huang; Qi Fu; Hao Wang; Ziye Zhang; Xiang Gao; Yinghui Liu; Hong Lin; Zhenxing Li (Food Bioscience, 2024)

Selective regulation of products for guaiacol hydrodeoxygenation by adjusting type and acidity of supports - Min Lin; Daxin Jiang; Yuhao Yan; Lulu Zhan; Xianliang Song; Rui Li; Yulong Wu (Bioresource Technology, 2024)

Synergistic chemical traction and pre-intercalation strategies enable high-quality MnO2 composites for efficient ammonium capture - Shiyong Wang; Shuwen Du; Yuhao Lei; Lin Zhao; Gang Wang (Chemical Engineering Journal, 2024)

Heat acclimation alleviates the heat stress-induced impairment of vascular endothelial cells - Jirui Wen; Zhengdong Lin; Juan Cheng; Can Li; Ling Wang; Yuhao Zou; Xuehong Wan; Jifeng Liu; Jiang Wu (Tissue and Cell, 2024)

Development of an indirect competitive ELISA based on the common epitope of fish parvalbumin for its detection - Yuhao Huang; Wenye Zhu; Yeting Wu; Lirui Sun; Qingli Li; Siddanakoppalu Narayana Pramod; Hao Wang; Ziye Zhang; Hong Lin; Zhenxing Li (Food Chemistry, 2024)

Hyper-Parameter Optimization-based multi-source fusion for remote sensing inversion of non-photosensitive water quality parameters - Yuhao Yuan; Zhiping Lin; Xinhao Jiang; Zhongmou Fan (International Journal of Remote Sensing, 2024)

MaHOS15 negatively regulates plant immune defense induced by banana fusarium wilt via salicylic acid pathway - Xingchen Jia; Kelin Chen; Yinglong Chen; Yi Tang; Hang Rong; Ping Lin; Yuhao Zhou; Chuqiao Wang; Mingyuan Wang; Jianfu Liu; Qizhi Wang; Hailing Yu (Physiological and Molecular Plant Pathology, 2024)

Influence of mountain orientation on precipitation isotopes in the westerly belt of Eurasia - Longhu Chen; Guofeng Zhu; Qin Qin Wang; Linlin Ye; Xinrui Lin; Siyu Lu; Yinying Jiao; Rui Li; Gaojia Meng; Yuhao Wang; Jiangwei Yang; Chen Jia (Global and Planetary Change, 2024)

Molecular mechanism of apoptosis induced by 4-tBP in common carp (Cyprinus carpio L.) head kidneys was explored from various angles: Hippo pathway, miR-203a, oxidative stress, ER stress, and mitochondrial pathway - Jiatian Liang; Xu Lin; Chunyu Jiang; Yuhao Liu; Zhiyu Hao; Minna Qiu; Xiumei Liu; Dechun Chen; Xiaohua Teng; You Tang (Aquaculture, 2024)

Retrieval and spatiotemporal variation of total suspended matter concentration using a MODIS-derived hue angle in the coastal waters of Qinhuangdao, China - Lin Wang; Xiang Wang; Qinghui Meng; Yanlong Chen; Xinxin Wang; Lingling Jiang; Yuhao Shang (Frontiers in Marine Science, 2024)
The CIE hue angle has significant potential in marine ecology and environment monitoring using remote sensing methods. It is calculated from the remote sensing reflectance ( R rs ) of all visible bands, which serves as a comprehensive indicator of seawater radiance information and represents one of the key quantitative parameters for assessing seawater color. In this study, a remote sensing retrieval model of total suspended matter concentration (TSM) was developed using the in situ measured data acquired in the coastal waters of Qinhuangdao from 2013 to 2021. This model, based on the CIE hue angle, achieved performance metrics of R 2 = 0.68, MAPE=24.47%, and RMSE=2.72 mg/L, demonstrating better accuracy than traditional empirical models that utilize fewer bands. Based on this model, the monthly and interannual TSM in the coastal waters of Qinhuangdao from 2003 to 2023 were retrieved. Influenced by natural factors, such as the monsoons, the TSM in the coastal waters of Qinhuangdao generally exhibited a trend of first decreasing and then increasing from January to December. Except for certain anomalous years (2007, 2008, 2017, etc.), the overall variation process of TSM from 2003 to 2023 showed an initial increase followed by a decrease, closely related to the pollution reduction management requirements implemented by the Chinese government in different periods. The findings of this paper demonstrate that the coastal waters of Qinhuangdao have become clearer, and the ecological environment has been effectively improved as a result of the Chinese government’s vigorous promotion of ecological civilization construction, adhering to the development concept that ‘lucid waters and lush mountains are invaluable assets’, and by introducing the action plan for the comprehensive treatment of pollution in the Bohai Sea.

The bioaugmentation effect of microbial inoculants on humic acid formation during co-composting of bagasse and cow manure - Mengling Lu; Yuhao Hao; Binfeng Lin; Zhi Huang; Yu Zhang; Liang Chen; Kai Li; Jianbin Li (Environmental Research, 2024)

Development of a fluorescent multiplexed lateral flow immunoassay for the simultaneous detection of crustacean allergen tropomyosin, sarcoplasmic calcium binding protein and egg allergen ovalbumin in different matrices and commercial foods - Yuhao Huang; Ranran Li; Wenye Zhu; Jinlong Zhao; Hao Wang; Ziye Zhang; Hong Lin; Wenjie Li; Zhenxing Li (Food Chemistry, 2024)

A celastrol-loaded DNA nano-patroller regulates hypothalamus leptin sensitivity and adipose energy expenditure for anti-obesity therapy - Yuhao Liu; Chongmai Zeng; Zhangheng Huang; Weijie Zhuang; Xiangyi Chen; Songhang Li; Zhiqiang Liu; Zhengwen Cai; Jianwei Zhu; Yunfeng Lin (Chemical Engineering Journal, 2024)

An oxidized dextran-composite self-healing coated magnesium scaffold reduces apoptosis to induce bone regeneration - Zewen Shi; Fang Yang; Yiwei Hu; Qian Pang; Lin Shi; Tianyu Du; Yuhao Cao; Baiyang Song; Xueqiang Yu; Zhaoxun Cao; Zhewei Ye; Chen Liu; et al. (Carbohydrate Polymers, 2024)

Temperature–Controlled hydrothermal hydrogenation of palmitic acid to alkanol or alkanes over Co@CN–x catalysts derived from ZIF–67 - Min Lin; Daxin Jiang; Yuhao Yan; Xiaoxian Li; Lulu zhan; Xianliang Song; Rui Li; Yulong Wu (Chemical Engineering Journal, 2024)

Temporal and spatial distribution and development of permanent gully in cropland in the rolling hill region (phaeozems area) of northeast China - Yuhao Gao; Yifan Zhu; Junxi Chen; Xue Yang; Yiting Huang; Fenghao Song; Yangbo He; Zhengchao Tian; Lirong Lin; Chongfa Cai; Jiazhou Chen (CATENA, 2024)

Integrated transcriptomic and metabolomic analysis reveals the potential mechanisms underlying indium-induced inhibition of root elongation in wheat plants - Ruyi Qian; Yihao Li; Yuhao Liu; Nan Sun; Lijuan Liu; Xianyong Lin; Chengliang Sun (Science of The Total Environment, 2024)

Complete genome sequence of Paris polyphylla chlorotic mottle virus infecting Paris polyphylla var. yunnanensis in southwest China - Qiongji He; Binghua Chen; Hongying Zheng; Yuhao Cao; Mengyin Hua; Yueyan Yin; Jiejun Peng; Junmin Li; Jianping Chen; Fei Yan; Xuemei Song; Lin Lin (Archives of Virology, 2023)

Encapsulation of lutein in gelatin type A/B-chitosan systems via tunable chains and bonds from tweens: Thermal stability, rheologic property and food 2D/3D printability - Hongxia Wang; Xianyou Lin; Juncheng Zhu; Yuxin Yang; Shihao Qiao; Bo Jiao; Liang Ma; Yuhao Zhang (Food Research International, 2023)

Insights into influence of CeO2 crystal structure effects on hydrothermal hydrogenation for palmitic acid over Ni/CeO2 catalysts - Min Lin; Yuhao Yan; Daxin Jiang; Xiaoxian Li; Rui Li; Yulong Wu (Chemical Engineering Journal, 2023)

The shock of benzalkonium chloride on aerobic granular sludge system and its microbiological mechanism - Yuhao Tong; Peili Lu; Wenyu Zhang; Jun Liu; Yuhai Wang; Lin Quan; Aqiang Ding (Science of The Total Environment, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Hydrothermal stable Ni nanoparticles encapsulated in carbon for hydrothermal hydrogenation of long-chain fatty acids to alkanes - Min Lin; Xiaoxian Li; Yuhao Yan; Rui Li; Yulong Wu (Chemical Engineering Journal, 2023)

3D lithiophilic framework fixed on the surface of LLZTO solid electrolyte shaping the contact between Li metal and ceramic - Yuhao Shi; Yifei Cai; Jiaqi Zhao; Tong Wu; Xiaoqian Xue; Tiesong Lin; Panpan Lin; Ce Wang; He Peng (Chemical Engineering Journal, 2023)

Site-specific labeling of antibodies with quantum dots could promote to retain the antigen binding capacity of antibodies - Yaoyang Zhang; Yuhao Huang; Ranran Li; Hao Wang; Ziye Zhang; Hong Lin; Zhenxing Li (Food Chemistry, 2023)

Cadmium exposure caused cardiotoxicity in common carps (Cyprinus carpio L.): miR-9-5p, oxidative stress, energetic impairment, mitochondrial division/fusion imbalance, inflammation, and autophagy - Yuhao Liu; Xu Lin; Zhiyu Hao; Meijin Yu; You Tang; Xiaohua Teng; Wei Sun; Lu Kang (Fish & Shellfish Immunology, 2023)

Orally administered BZL-sRNA-20 oligonucleotide targeting TLR4 effectively ameliorates acute lung injury in mice - Dandan Zhao; Yuhao Qin; Jiaqi Liu; Kegong Tang; Shuaiyao Lu; Zirui Liu; Yexuan Lin; Cong Zhang; Fengming Huang; Jiahui Chang; Chang Li; Mingyao Tian; et al. (Science China Life Sciences, 2023)

CNT/copper hexacyanoferrate: A superior Faradic electrode for ammonium ion removal with stable performance and high capacity - Shiyong Wang; Zhihao Pan; Zhuo Li; Haohong Zhuang; Lin Zhao; Zhuolin Li; Yuhao Lei; Gang Wang (Chemical Engineering Journal, 2023)

Numerical study on the performance of the thermoelectric generator with different air-water mixtures - Haozhe Zhang; Kewen Li; Yuhao Zhu; Lin Jia (Geothermics, 2023)

Soil moisture dynamics near a gully head in relation to the trigger of collapse in granite red soil slope in southern China - Ziqiang Zou; Yu Tao; Yuhao Gao; Zixuan Liu; Wenkai Li; Zhengchao Tian; Lirong Lin; Yangbo He; Jiazhou Chen (Geomorphology, 2023)

Lamellar-structured anodes based on lithiophilic gradient enable dendrite-free lithium metal batteries with high capacity loading and fast-charging capability - Yucheng Liu; Chuang Sun; Yuhao Lu; Xiaoping Lin; Maohua Chen; Yuansen Xie; Chao Lai; Wen Yan (Chemical Engineering Journal, 2023)

Safety and efficacy of new oral anticoagulants compared to those of warfarin in AF patients with cancer: a meta-analysis of randomized clinical trials and observational studies - Yueming Chen; Min Mao; Jing Chang; Jing Yan; Tiantian Yang; Yang Liu; Meng Luo; Yuhao Hu; Qi Yang; Lin Zhou; Kanghua Ma (European Journal of Clinical Pharmacology, 2021)

Complete genome sequence of passiflora virus Y infecting passion fruit in China - Binghua Chen; Dali Wu; Hongying Zheng; Guangze Li; Yuhao Cao; Jianping Chen; Fei Yan; Xuemei Song; Lin Lin (Archives of Virology, 2021)

Large-scale analysis of small RNAs derived from traditional Chinese herbs in human tissues - Fengming Huang; Jianchao Du; Zhu Liang; Zhichao Xu; Jiantao Xu; Yan Zhao; Yexuan Lin; Song Mei; Quan He; Jindong Zhu; Qiang Liu; Yanxu Zhang; et al. (Science China Life Sciences, 2019)